Исследование кристаллической и магнитной структур манганита Pr₀.₇Ba₀.₃MnO₃ под высоким давлением - Труханов, А.В.; Козленко, Д.П.; Чан, Т.А.; Труханов, С.В.; Кичанов, С.Е.; Васильев, А.Н. (Физика и техника высоких давлений, 2012)
Методом нейтронной дифракции исследованы кристаллическая и магнитная структуры анион-стехиометрического манганита Pr0.70Ba0.30MnO3 в диапазоне давлений 0−5 GPa и температур 10–300 K. Определены барические зависимости параметров и объема элементарной ячейки, межатомных связей Mn−O в орторомбической структуре симметрии Imma. При давлении Р = 1.9 GPa в области низких температур обнаружен магнитный фазовый переход из ферромагнитного (ФМ) состояния (ТC ~ 197 K) в антиферромагнитное (АФМ) А-типа (ТN ~ 153 K). Ферро- и антиферромагнитная фазы сосуществуют в диапазоне давлений до P ~ 5.1 GPa. Рассчитаны барические коэффициенты для ФМ- и АФМ-фаз. Методом нейтронної дифракції досліджено кристалічну та магнітну структури аніон-стехіометричного манганіту Pr0.70Ba0.30MnO3 в діапазоні тиску 0−5 GPa і температур 10–300 K. Визначено баричні залежності параметрів й об'єму елементарної комірки, міжатомних зв'язків Mn−O в орторомбічній структурі симетрії Imma. При тиску Р = 1.9 GPa в області низьких температур виявлено магнітний фазовий перехід із феромагнітного (ФМ) стану (ТС ~ 197 K) в антиферомагнітний (АФМ) А-типу (ТN ~ 153 K). Феро- й антиферомагнітна фази співіснують у діапазоні тиску до P ~ 5.1 GPa. Розраховано баричні коефіцієнти для ФМ- і АФМ-фаз. The recent studies have shown that in manganites Nd(Sm)0.50Ba0.50MnO3, application of high hydrostatic pressure up to P ~ 5 GPa results in ferromagnetism and suppresses spin glass state. It can be assumed that the application of high pressures P > 1 GPa to Pr₀.₇Ba₀.₃MnO₃ can also cause changes in the magnetic structure with emergence of the antiferromagnetic (AFM) phase, as is observed in the case of La₀.₇₅Ca₀.₂₅MnO₃. At normal pressure and temperatures below T ~ 197 K, the increase in the intensity of the (200)/(002)/(121) and (101)/(020) diffraction peaks located at d ~ 2.78 and ~ 3.91 Å is observed, which indicates formation of the main ferromagnetic state. The magnetic moment of the manganese ion at 10 K is ~ 3.6(1)μB. When the pressure rises, anisotropic compression of the oxygen octahedra along b axis occurs. The mean value of the Mn−O−Mn bond angle decreases from 166.0 to 165.7°. At temperatures below T = 153 K, the emergence of new (010) and (111) magnetic reflections at d ~ 7.50 and ~ 3.44 Å is detected, which corresponds to appearance of a new AFM-phase with the A-type ordering, which coexists with the FM-phase. The magnetic moments of the manganese of AFM-phase are in the ac planes. They are oriented parallel to each other within these planes and change its direction on the opposite one in the neighbor planes perpendicular to the b plane of the orthorhombic structure. The values of the magnetic moment of Mn at T = 10 K are ~ 3.2(1)μB (for FM-phase) and ~ 1.8(1)μB (for the AFM-phase). With increasing pressure, the reduction of the Curie temperature from 197 K (P = 0) to 185 K (P = 5.1 GPa) occurs with negative dTC/dP = −2.3 K/GPa pressure coefficient. In this case, the Neel temperature increases from 153 K (P = 1.9 GPa) to 179 K (P = 5.1 GPa) with positive dTN/dP = 8 K/GPa pressure coefficient. The negative pressure coefficient for the FM-phase is likely determined by the reduction of Mn−O−Mn angle and consequently by decrease of the zone of charge carriers. The results of these studies demonstrate, that high-pressure effect on Pr₀.₇Ba₀.₃MnO₃ suppresses the initial FM state and generates the AFM state of A-type, which is due to the anisotropic compression of the oxygen octahedra. The observed behavior of TC is very different from that of other manganites, such as La₀.₇Sr₀.₃MnO₃ and La₀.₇₅Ca₀.₂₅MnO₃ with orthorhombic (Pnma) and rhombohedral (R3c) structures where the increase of the Curie temperature with large pressure coefficients is detected at high pressure effect.